Antifungal Factor Produced by Pseudomonas fluorescens against an Endophytic Fungus - Malla, Rajani; Pokharel, Suprada (Nepal Journal of Science and Technology, 2010)
Growth characteristics of Piriformospora indica an endophytic fungus with plant growth promoting rhizobacteria in an aspergillus medium were studied. P. indica showed promotional effects with species of Azotobacter chroococcum, Azospirillum brasilensis, Bradyrhizobium spp., and inhibitory effect with Pseudomonas fluorescens. The biochemical and molecular level of inhibitory factor produced by P. fluorescence suggests that the antifungal substance was thermolabile and the protease test showed it to be protease resistant in nature. Dialysis test indicated that this substance had a molecular weight of more than 12,000 kDa. The inhibitory substance turns out to be 'fungistatic' as well as 'fungicidal' in nature. Scanning electron microscopy (SEM) and Transmission electron microscopy (TEM) studies showed the cell wall in damaged form suggesting the high potency of this antifungal substance. The inhibitory compound produced by P. fluorescence was suspected to be pyoverdine, a kind of siderophore, an iron containing substance. Key words: Pseudomonas fluorescens; Piriformospora indica; siderophore; rhizobacteria; TEM; SEM DOI: 10.3126/njst.v9i0.3167 Nepal Journal of Science and Technology 9 (2008) 65-71